The Pharmaceutical and Pharmacological Potential Applications of Bilosomes as Nanocarriers for Drug Delivery - Darko Mitrović; Dragana Zaklan; Maja Đanić; Bojan Stanimirov; Karmen Stankov; Hani Al-Salami; Nebojša Pavlović (Molecules)
Nano-drug delivery systems provide targeted solutions for addressing various drug delivery challenges, leveraging nanotechnology to enhance drug solubility and permeability. Liposomes, explored for several decades, face hurdles, especially in oral delivery. Bile-acid stabilized vesicles (bilosomes) are flexible lipid vesicles, composed of phospholipids or other surfactants, along with amphiphilic bile salts, and they show superior stability and pharmacokinetic behavior in comparison to conventional vesicular systems (liposomes and niosomes). Bilosomes enhance skin penetration, fluidize the stratum corneum, and improve drug stability. In oral applications, bilosomes overcome drawbacks, offering improved bioavailability, controlled release, and reduced side effects. Vaccines using bilosomes demonstrate efficacy, and bilosomes for intranasal, inhalation, ocular, and buccal applications enhance drug delivery, offering targeted, efficient, and controlled activities. Formulations vary based on active substances and optimization techniques, showcasing the versatility and potential of bilosomes across diverse drug delivery routes. Therefore, the aim of this comprehensive review was to critically explore the state-of-the-art of bilosomes in drug delivery and potential therapeutic applications.